1992
DOI: 10.1080/02650539208413495
|View full text |Cite
|
Sign up to set email alerts
|

Some obstacles to the effective investigation and registration of children at risk—issues gleaned from a worker's perspective

Abstract: How can front-line practitioners be helped to c a r y out their responsibilities for child protection? This paper outlines and discusses some of the findings which emerged from interviews with 20 social workers about their involvement in regktration decisions. In particular it considers obstacles io effective investigation and decision making, highlighting factors associated with the cases, the workers' knowledge base and the professional support available.Our findings suggest a scenario in which social worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Given the existence of a wealth of good practice guidance about how to be an effective supervisor and the evidence that supervision is such a critical forum through which the high levels of anxiety inherent in the work can be confronted and contained, it is disturbing to find such a preponderance of evidence which suggests many workers are receiving insufficient supervision and that they are dissatisfied with the quality of what they get (Gibson et al, 1989; 'Evidence suggests many workers are receiving insufficient supervision and they are dissatisfied with the quality of what they get' Marsh and Triseliotis, 1996;Auditor General's Report, 1996). Rather than concentrating on the development of effective supervision structures to assist workers to function in such a personally and professionally demanding world, the literature indicates that public child welfare organizations have concentrated more on the issue of accountability, with the proliferation of policies and procedures being the predominant response (Howe, 1992;Bingley Miller and Fisher, 1992;Hough, 1995). Without suggesting that policies and procedures have no value, Bingley Miller and Fisher (1992, p. 136) point out that they cannot usually assist with the impact of emotion on workers' perceptions and actions or gaps in their knowledge and skill.…”
Section: Supervision In Child Protectionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the existence of a wealth of good practice guidance about how to be an effective supervisor and the evidence that supervision is such a critical forum through which the high levels of anxiety inherent in the work can be confronted and contained, it is disturbing to find such a preponderance of evidence which suggests many workers are receiving insufficient supervision and that they are dissatisfied with the quality of what they get (Gibson et al, 1989; 'Evidence suggests many workers are receiving insufficient supervision and they are dissatisfied with the quality of what they get' Marsh and Triseliotis, 1996;Auditor General's Report, 1996). Rather than concentrating on the development of effective supervision structures to assist workers to function in such a personally and professionally demanding world, the literature indicates that public child welfare organizations have concentrated more on the issue of accountability, with the proliferation of policies and procedures being the predominant response (Howe, 1992;Bingley Miller and Fisher, 1992;Hough, 1995). Without suggesting that policies and procedures have no value, Bingley Miller and Fisher (1992, p. 136) point out that they cannot usually assist with the impact of emotion on workers' perceptions and actions or gaps in their knowledge and skill.…”
Section: Supervision In Child Protectionmentioning
confidence: 97%
“…A lack of attention and response to the often unconscious defence mechanisms adopted by individuals to survive in the face of 'Often unconscious defence mechanisms adopted by individuals to survive' high levels of anxiety and distress become damaging to those individuals, and potentially dangerous for the children and families who come within the remit of protective services (Dale et al, 1986;Bingley Miller and Fisher, 1992;Stanley and Goddard, 1993;Fitzgerald and McGregor, 1995).…”
mentioning
confidence: 97%
“…is the chair's ability to facilitate the expression of dissent when it is hovering in the air but has not been articulated. ' (p. 234) One possible explanation for the lack of disagreement may stem from the difficulties faced by social workers in being 'judgemental' at case conferences (Miller and Fisher, 1992). Pecora (1991) concluded that formal risk assessment could be an important tool in improving decision-making, perhaps pointing to the need for training in risk assessment, as well as the development of practical methods.…”
mentioning
confidence: 98%
“…In short, in time-constrained environments, child protection staff need institutional support for reasoned decision making. Such support may take the form of organizational structures and/or emotional scaffolding upon which staff can rely (Miller & Fisher, 1992) and be held accountable.…”
Section: Time Institutional Support and Quality In Bureaucratic Conmentioning
confidence: 99%
“…In short, in time-constrained environments, child protection staff need institutional support for reasoned decision making. Such support may take the form of organizational structures and/or emotional scaffolding upon which staff can rely (Miller & Fisher, 1992) and be held accountable.Accountability is a central concern in child protection in part because of the gravity and consequences of these public actors' decisions; the power interplay between child protection staff and the typically marginalized populations served by child welfare; and the contested nature of interventions into the private sphere. Accountability is commonly used as a standard for good governance (Bovens, 2007) and includes concepts such as transparency, legitimacy, trustworthiness, responsiveness, and justice (Bovens, 2007;Mulgan, 2000).…”
mentioning
confidence: 99%